2012
DOI: 10.1098/rsbl.2012.0112
|View full text |Cite
|
Sign up to set email alerts
|

Habitat associations of species show consistent but weak responses to climate

Abstract: Different vegetation types can generate variation in microclimates at local scales, potentially buffering species from adverse climates. To determine if species could respond to such microclimates under climatic warming, we evaluated whether ectothermic species (butterflies) can exploit favourable microclimates and alter their use of different habitats in response to year-to-year variation in climate. In both relatively cold (Britain) and warm (Catalonia) regions of their geographical ranges, most species shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 10 publications
2
70
0
Order By: Relevance
“…Considering that only a small proportion of total land area can ever be realistically protected in the form of nature reserves, conservation efforts must also comprise the surrounding area of nature reserves considering all components of biodiversity [29]. This becomes particularly important in a changing climate scenario, when species – as we have shown here for butterflies – may leave existing nature reserves or alter their habitat associations in search of more climatically-suitable habitats [18], [68].…”
Section: Discussionmentioning
confidence: 95%
“…Considering that only a small proportion of total land area can ever be realistically protected in the form of nature reserves, conservation efforts must also comprise the surrounding area of nature reserves considering all components of biodiversity [29]. This becomes particularly important in a changing climate scenario, when species – as we have shown here for butterflies – may leave existing nature reserves or alter their habitat associations in search of more climatically-suitable habitats [18], [68].…”
Section: Discussionmentioning
confidence: 95%
“…For example, Suggitt et al (2012) found that butterflies occurring in Illán et al, 2012), these rates are unlikely to represent fixed attributes of the species. seed production as the climate has warmed (Steltzer & Post, 2009).…”
Section: Date Of Appearancementioning
confidence: 99%
“…Determining if these changes in distribution will be fast enough to cope with current climate change, or conversely if species and communities are acquiring climatic debts, is therefore crucial [94]. Ample evidence suggests that these distributional changes are ultimately influenced by microclimatic effects, behavioral buffering and genetic and epigenetic adaptations [95][96][97][98][99]. Biotic interactions can also strongly modify the species-specific capacity to disperse and thus should also be included for developing more robust models for predicting future species distributions [100].…”
Section: Changes In Morphology Physiology Phenology and Growth In Amentioning
confidence: 99%